The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e04635
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of sky brightness at Bosscha Observatory, Indonesia

Abstract: To determine the level of light pollution due to human activities, we performed sky-brightness measurements at Bosscha Observatory, Indonesia (107°36′E; 6°49′S, 1300 m above sea level) for seven years from 2011 to 2018, using a portable photometer pointed at the zenith. From 1692 nightly records, we found that the average brightness on moonless nights reached the 19.70 ± 0.84 and 19.01 ± 0.88 astronomical magnitudes per square arcsecond (mpass), with median values of 19.73 mpass and 19.03 mpass for the AM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…This is reasonable since systematic darkening rarely occurs in rural areas, while in urban areas, the darkening can be 0.14 mpsas/hour (Posch et al 2018). In line with that, Herdiwijaya et al (2020) found a ∼0.7 mpsas deviation between pre-and post-midnight sky brightness over Bosscha Observatory, where light pollution from surrounding urban areas is inevitable.…”
Section: General Statisticssupporting
confidence: 79%
“…This is reasonable since systematic darkening rarely occurs in rural areas, while in urban areas, the darkening can be 0.14 mpsas/hour (Posch et al 2018). In line with that, Herdiwijaya et al (2020) found a ∼0.7 mpsas deviation between pre-and post-midnight sky brightness over Bosscha Observatory, where light pollution from surrounding urban areas is inevitable.…”
Section: General Statisticssupporting
confidence: 79%
“…Light pollution in the vicinity of the Bosscha Observatory could account for this pattern. [12], which are 19.70 ± 0.84 and 19.01 ± 0.88 mpass. The relation between sky brightness and the month of observation also investigated by [12].…”
Section: Resultsmentioning
confidence: 95%
“…It can be seen that fluctuations begin to occur at 8 a.m. coinciding with the shadow length of the object being 1.3 meters. In the afternoon curve, the start of fluctuations is difficult to detect due to the clouds that always appear after noon for semidiurnal pattern, as seen in Figure 2 [9]. When the shadow length is 1, both sky brightness values are the same.…”
Section: Figure 2 Sky Brightness Difference Curve In the Morning And ...mentioning
confidence: 98%